PENGEMBANGAN METODE PEMBELAJARAN KESELAMATAN DAN KESEHATAN KERJA DI PPSDM GEOLOGI, MINERAL, DAN BATUBARA - Harry Wibawa (PPSDM Geominerba, 2017)
Human Resources Development Center of Mineral Geology and Coal (PPSDM Geominerba), as an institution that conducts education and training for mineral and coal subsector owns an important role in reinforcing the improvement of workplace safety and health (K3). PPSDM Geominerba is wished to give high quality education and training, not only theoretically but also practically, through practical and applied activity in order to give full awareness and concern for the employee in improving workplace safety and health. So far, the activity of K3 training is conducted by using lecturing method in the classroom, and it does not combinetheoretical and practical knowledge. Hence, the learning outcomes are not enough to give experience, life skill, and motivation for the participants of training. For that reason, it is important to develop a method to learn K3 that is able to integrate and apply contextual knowledge or skill, so participants will be able to apply the knowledge to achieve the goal of K3 in their workplace. Learning method that should be improved covers the combination of lecture, discussion, practice, role play, observation and discussion, or by using other applicable combination. For cognitive learning objective, it is good to combine lecture, Q&A, and discussion. Training material that needs participant’s psychomotor skill can be taught by practical method. These methods aresuggested to give participants direct experience and to make them capable to apply the knowledge and skill in their workplace.